Promoting Students Critical Thinking and Cognitive Learning Outcomes through Problem-Based Learning integrated with Mind-Mapping - Lianto, Lianto; Rohayati, Yulista Trias (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Critical thinking and advanced cognitive abilities are vital competencies in 21st-century biology education, especially in complicated subjects like immunology. Innovative pedagogical methods are crucial for helping pupils overcome learning challenges and develop a deep understanding. This study examines the integration of problem-based learning (PBL) with mind-mapping approaches to enhance undergraduates' critical thinking and cognitive learning in immunology education, a field often regarded as complex and interdisciplinary. A quasi-experimental one-group pretest-posttest design was utilized, comprising 23 undergraduate students participating in a fundamental immunology course at the State University of Malang, Indonesia. Data were gathered using essay-based evaluations and evaluated employing paired t-tests, N-gain scores, and effect size computations. The results demonstrated substantial enhancements in both critical thinking and cognitive learning outcomes post-intervention, with impact sizes classified as big to very large. The extent of improvement differed among indicators, exhibiting moderate advancements in applying, evaluating, and analyzing, whereas synthesis showed only modest advancement. The results indicate that PBL combined with mind-mapping can effectively enhance higher-order thinking skills in complex subjects, providing dual scaffolding that aids students in organizing intricate concepts, visualizing relationships, and reinforcing higher-order thinking abilities.